2013
DOI: 10.1016/j.jns.2013.07.1952
|View full text |Cite
|
Sign up to set email alerts
|

The second face of blindness: Processing speed deficits in the intact visual field after pre- and post-chiasmatic lesions

Abstract: Purpose: Damage along the visual pathway results in a visual field defect (scotoma), which retinotopically corresponds to the damaged neural tissue. Other parts of the visual field, processed by the uninjured tissue, are considered to be intact. However, perceptual deficits have been observed in the ''intact'' visual field, but these functional impairments are poorly understood. We now studied temporal processing deficits in the intact visual field of patients with either pre-or postchiasmatic lesions to bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 58 publications
2
6
0
Order By: Relevance
“…Regarding visual detection and analysis, Paramei and Sabel (2008) reported that these patients exhibited diminished abilities to detect fragmented targets among a noisy background in the IVF, whereas Schadow et al (2009) found deficits in the early and late visual processing of Gestalt patterns in the IVF. More recently, Bola et al (2013b) confirmed these findings and reported processing-speed deficits in a simple detection task in the IVF. The authors termed this phenomenon sightblindness , as the reverse situation of blindsight ( Bola et al, 2013a ): the former refers to visuo-attentional deficits in the IVF, whereas the latter refers to residual (although implicit) visual abilities in the contralesional visual field (CVF) that are highlighted in forced-choice tasks (e.g., Weiskrantz et al, 1974 ).…”
Section: Less-studied Consequences Of Unilateral Occipital Lesionssupporting
confidence: 55%
See 2 more Smart Citations
“…Regarding visual detection and analysis, Paramei and Sabel (2008) reported that these patients exhibited diminished abilities to detect fragmented targets among a noisy background in the IVF, whereas Schadow et al (2009) found deficits in the early and late visual processing of Gestalt patterns in the IVF. More recently, Bola et al (2013b) confirmed these findings and reported processing-speed deficits in a simple detection task in the IVF. The authors termed this phenomenon sightblindness , as the reverse situation of blindsight ( Bola et al, 2013a ): the former refers to visuo-attentional deficits in the IVF, whereas the latter refers to residual (although implicit) visual abilities in the contralesional visual field (CVF) that are highlighted in forced-choice tasks (e.g., Weiskrantz et al, 1974 ).…”
Section: Less-studied Consequences Of Unilateral Occipital Lesionssupporting
confidence: 55%
“…Conversely to the case of blindsight, which has been extensively studied in hemianopia patients, vision quality in the central visual field and in the IVF of these patients has scarcely been assessed, and moreover, it has traditionally been assumed to remain intact. However, as recently proposed, neither the central visual field ( Cavézian et al, 2010 ; Perez et al, 2013 ), nor the IVF of hemianopic patients ( Bola et al, 2013a , b , Clatworthy et al, 2013 ; Cavézian et al, 2015 ) actually appear to be fully intact or functional. Moreover, as we recently proposed, and as discussed below, the nature of the task, the type of stimulus and the side of the occipital lesion might determine the central and ipsilesional visual deficit in hemianopic patients ( Cavézian et al, 2010 , 2015 ; Perez et al, 2013 ).…”
Section: Less-studied Consequences Of Unilateral Occipital Lesionsmentioning
confidence: 83%
See 1 more Smart Citation
“…Although our patients all performed at ceiling for detection of 1% contrast in their intact visual field, slight differences in fMRI responses compared with controls could reflect impairments in this mechanism. However, the importance of scotoma size (and thus probably lesion size) on the degree of impairment and the lack of any difference when comparing retinotopically equivalent responses with nonequivalent regions in a large group of quadrantanopes (Bola et al, 2013) suggest a more global effect that may reflect additional regions of cortical damage.…”
Section: Intact Hemisphere Responses For the Sighted Field Are Mostlymentioning
confidence: 99%
“…The fact that detection accuracy gains in glaucoma were not predominantly found in ARVs (as was seen in hemianopia 6 ) suggests that surviving retinal ganglion cells deep in the damaged zones might contribute to vision restoration or changes in intact visual field sectors. 66,67 To clearly delineate the mechanisms of vision restoration requires further study using an electroencephalogram or magnetic resonance imaging recordings.…”
Section: Research Original Investigationmentioning
confidence: 99%